2019
DOI: 10.1155/2019/1534365
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignant Neoplasia with Glucagon-Like Peptide-1 Receptor Agonist Treatment in Patients with Type 2 Diabetes: A Meta-Analysis

Abstract: Background. Glucagon-like peptide-1 (GLP-1) receptor agonists are effective glucose-lowering drugs, but there is concern that they may increase the risk of malignant neoplasia. The present meta-analysis examined the safety of GLP-1 receptor agonists with regard to malignant neoplasia. Methods. We analyzed data from randomized controlled trials with a minimum duration of 24 weeks that assessed the incidence of neoplasms in type 2 diabetes patients receiving GLP-1 receptor agonists compared with placebo or other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“… 3 A meta-analysis including 3446 patients treated with subcutaneous semaglutide for up to 104 weeks and 419 patients treated with oral semaglutide for 26 weeks concluded that there was no increased risk of malignant neoplasms with semaglutide when compared with placebo or other glucose-lowering treatments (OR (95% CI) 0.89 (0.35 to 2.22); p=0.80). 19 Consistent with other studies of oral semaglutide, 1–10 no clustering of malignancies to specific organ systems was observed.…”
Section: Discussionsupporting
confidence: 89%
“… 3 A meta-analysis including 3446 patients treated with subcutaneous semaglutide for up to 104 weeks and 419 patients treated with oral semaglutide for 26 weeks concluded that there was no increased risk of malignant neoplasms with semaglutide when compared with placebo or other glucose-lowering treatments (OR (95% CI) 0.89 (0.35 to 2.22); p=0.80). 19 Consistent with other studies of oral semaglutide, 1–10 no clustering of malignancies to specific organ systems was observed.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in a large interventional study of 9341 participants with type 2 diabetes, liraglutide treatment did not increase neoplasm incidence [ 82 ]. This conclusion was supported by a meta-analysis including 50,453 patients from randomized controlled trials, assessing the incidence of neoplasms in type 2 diabetic patients receiving GLP-1 receptor agonists compared with placebo or other hypoglycemic drugs; in this study, there was no increase in malignant neoplasm formation upon GLP-1 agonist use [ 83 ].…”
Section: Theoretical Drug Safety Of Glp-1mentioning
confidence: 73%
“…Meta-analyses, as well as information collected from CVOTs involving long-term follow-up of thousands of patients, have consistently found insufficient evidence to support an increased risk of acute pancreatitis or cancer (including thyroid cancers) associated with GLP-1RAs as a class [48][49][50]. This was also suggested by data from PIONEER 6, in which acute pancreatitis was confirmed in one patient treated with oral semaglutide, and three patients receiving placebo [25].…”
Section: Adverse Events and Safetymentioning
confidence: 99%